Effects of short-term exposure to air pollution on hospital admissions for autism spectrum disorder in Korean school-aged children: a nationwide time-series study - Kim, Kyoung Nam; Sohn, Ji Hoon; Cho, Sung Joon; Seo, Hwo Yeon; Kim, Soontae; Hong, Yun Chul (BMJ Open, 2022)
Objectives This study explored the effects of short-term exposure to air pollution on hospital admissions for autism spectrum disorder (ASD), a proxy for symptom aggravation, among Korean children aged 5-14 years. Design Time-series study. Setting, participants and outcome measures We used data from the National Health Insurance Service (2011-2015). Daily concentrations of fine particulate matter (PM 2.5), nitrogen dioxide (NO 2) and ozone (O 3) levels in each region were used as exposures. ASD cases were defined based on a principal admission diagnosis of the claims data. We applied distributed lag non-linear models and a generalised difference-in-differences method to the quasi-Poisson models to estimate the causal effects of air pollution for up to 6 days. We also performed weighted quantile sum regression analyses to assess the combined effects of air pollution mixtures. Results PM 2.5 levels at lag day 1, NO 2 levels at lag day 5 and O 3 levels at lag day 4 increased the risks of hospital admissions for ASD (relative risk (RR)=1.17, 95% CI 1.10 to 1.25 for PM 2.5; RR=1.09, 95% CI 1.01 to 1.18 for NO 2 and RR=1.03, 95% CI 1.00 to 1.06 for O 3). The mean daily count of hospital admissions for ASD was 8.5, and it would be 7.3, 7.8 and 8.3 when the PM 2.5 levels would be decreased by 10.0 μg/m 3, NO 2 by 10 ppb and O 3 by 10 ppb, respectively. The weighted quantile sum index, constructed from PM 2.5, NO 2 and O 3 levels, was associated with a higher risk of hospital admissions for ASD (RR 1.29, 95% CI 1.14 to 1.46), where NO 2 was found to contribute to the effects most (the weight of 0.80). Conclusions These results emphasise that reduction of air pollution exposure should be considered for ASD symptom management, with important implications for the quality of life and economic costs.
Keywords: Air Pollution; Autism Spectrum Disorder; Child; Hospitals; Humans; Nitrogen Dioxide; Ozone; Particulate Matter; Quality of Life; Republic of Korea; child & adolescent psychiatry; epidemiology; mental health; public health